Mesenchymal Stem Cells in the Adult Human Liver: Hype or Hope? - Irina V. Kholodenko; Leonid K. Kurbatov; Roman V. Kholodenko; Garik V. Manukyan; Konstantin N. Yarygin (Cells, 2019)
Chronic liver diseases constitute a significant economic, social, and biomedical burden. Among commonly adopted approaches, only organ transplantation can radically help patients with end-stage liver pathologies. Cell therapy with hepatocytes as a treatment for chronic liver disease has demonstrated promising results. However, quality human hepatocytes are in short supply. Stem/progenitor cells capable of differentiating into functionally active hepatocytes provide an attractive alternative approach to cell therapy for liver diseases, as well as to liver-tissue engineering, drug screening, and basic research. The application of methods generally used to isolate mesenchymal stem cells (MSCs) and maintain them in culture to human liver tissue provides cells, designated here as liver MSCs. They have much in common with MSCs from other tissues, but differ in two aspects—expression of a range of hepatocyte-specific genes and, possibly, inherent commitment to hepatogenic differentiation. The aim of this review is to analyze data regarding liver MSCs, probably another type of liver stem/progenitor cells different from hepatic stellate cells or so-called hepatic progenitor cells. The review presents an analysis of the phenotypic characteristics of liver MSCs, their differentiation and therapeutic potential, methods for isolating these cells from human liver, and discusses issues of their origin and heterogeneity. Human liver MSCs are a fascinating object of fundamental research with a potential for important practical applications.